2012
DOI: 10.1002/anie.201107376
|View full text |Cite
|
Sign up to set email alerts
|

Porous Single‐Crystalline Palladium Nanoparticles with High Catalytic Activities

Abstract: Palladium's pore cousin: a facile approach is described for the size-controlled preparation of porous single-crystalline Pd nanoparticles. These porous Pd nanoparticles exhibit size-independent catalytic activities for the Suzuki coupling and are more active than commercial Pd/C catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
127
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(132 citation statements)
references
References 37 publications
5
127
0
Order By: Relevance
“…Nowadays, exponentially expanded nanotechnology has certified that the morphologies of nanoparticles dramatically affect the catalytic properties of catalysts [9]. Among diverse morphologies, oriented attachment of small nanoparticles into three-dimensional (3D) nanostructures as nanocatalysts is a hotspot owing to their rough surfaces, abundant defect sites, and cooperative interactions between the building blocks [10][11][12][13][14]. Our group successfully introduced the 3D nanostructures of PdAu and PdAg catalysts into the selective hydrogenation of acetylene, and these catalysts exhibited preferred activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, exponentially expanded nanotechnology has certified that the morphologies of nanoparticles dramatically affect the catalytic properties of catalysts [9]. Among diverse morphologies, oriented attachment of small nanoparticles into three-dimensional (3D) nanostructures as nanocatalysts is a hotspot owing to their rough surfaces, abundant defect sites, and cooperative interactions between the building blocks [10][11][12][13][14]. Our group successfully introduced the 3D nanostructures of PdAu and PdAg catalysts into the selective hydrogenation of acetylene, and these catalysts exhibited preferred activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting 3D nanostructures are generally characterized by rough surfaces, high porosity, high densities of crystalline defects, and complex morphologies, with cooperative effects between the building blocks [24][25][26][27][28][29][30]. For example, a porous Pd catalyst showing high catalytic activity in the Suzuki coupling reaction has been reported, and the high activity was attributed to the high concentration of low-coordinate surface atoms [27]. Moreover, Yang et al found that tetradecyltrimethylammonium bromide-capped porous Pt particles exhibited superior catalytic activity in ethene hydrogenation compared with polyvinylpyrrolidone-capped Pt cubes and cuboctahedra [24].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the formation of highly branched nanostructures requires growth under conditions that typically favour kinetic products. To date, a range of branched nanostructures have been synthesized for various noble metals, including Pt, [27][28][29] Pd, 3,[30][31][32] Au, 33,34 Ag, 35 and Ru. 36 However, the fast rate of kinetically controlled growth makes it difficult to control the final particle size, with branched structures >100 nm being produced.…”
Section: -26mentioning
confidence: 99%
“…In industry, palladium is used extensively as a heterogeneous catalyst, especially for the reduction of automobile emissions, 1 and for carbon-carbon cross-coupling reactions such as Suzuki, [2][3][4][5] Heck, 6,7 and Stille coupling. 8,9 Suzuki cross-coupling reactions are one of the most widely implemented methods used in the formation of carbon-carbon bonds, and are also very efficient under heterogeneous catalysis conditions.…”
Section: Introductionmentioning
confidence: 99%